Introduction to Discrete Signal Processing - Lindig Bos, Miguel (Revista Mexicana de Ingenieria Biomedica, 2018)
The present tutorial aims to complete an Introduction to Discrete Signal Processing. This introduction started with an article published in Vol. 2, No. 1 of this journal. In this article the reader will be introduced to the fundamental concepts of spectral analysis as a tool in signal analysis. We will describe the different types of spectrum analysers as well as the corresponding mathematical algorithms. We well briefly mention some of the applications and practical problems of spectral analysis.